Bartolomé de Alcázar y el "De Ratione Dicendi" (1681-1688) - López Muñoz, Manuel (Euphrosyne: Revista de filología clássica, 2018)
This paper describes Bartolomé de Alcázar’s De ratione dicendi (1681-1688), a treatise composed of an abridged Aphthonius, a small De conscribendis epistolis and aDe rhetorica facultate. After some considerations on the evolution and structure of the text, the work is presented in the context of the Jesuit Ratio Studiorum.